2004
DOI: 10.1099/ijs.0.02754-0
|View full text |Cite
|
Sign up to set email alerts
|

Wautersia gen. nov., a novel genus accommodating the phylogenetic lineage including Ralstonia eutropha and related species, and proposal of Ralstonia [Pseudomonas] syzygii (Roberts et al. 1990) comb. nov.

Abstract: Culture Collection of the University of Gøteborg, Gøteborg, SwedenComparative 16S rDNA sequence analysis indicates that two distinct sublineages, with a sequence dissimilarity of >4 % (bootstrap value, 100 %), exist within the genus Ralstonia: the Ralstonia eutropha lineage, which comprises Ralstonia basilensis, Ralstonia campinensis, R. eutropha, Ralstonia gilardii, Ralstonia metallidurans, Ralstonia oxalatica, Ralstonia paucula, Ralstonia respiraculi and Ralstonia taiwanensis; and the Ralstonia pickettii lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(129 citation statements)
references
References 42 publications
3
117
0
9
Order By: Relevance
“…In 1999, C. pauculus was firstly described as Ralstonia paucula; the description was identical to the one given by Vaneechoutte et al in 2004 as Wautersia paucula, and it was finally renamed C. pauculus. C. pauculus is an oxidase, catalase, citrate, and urea positive motile and non-fermentatile bacillus (7,8). This bacillus can be distinguished from R. pickettii, R. gilardii, and R. mannitolilytica by biochemical tests (nitrate reduction, carbohydrate acidification, urease, and fatty acid profile) and conclusively by DNA sequencing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In 1999, C. pauculus was firstly described as Ralstonia paucula; the description was identical to the one given by Vaneechoutte et al in 2004 as Wautersia paucula, and it was finally renamed C. pauculus. C. pauculus is an oxidase, catalase, citrate, and urea positive motile and non-fermentatile bacillus (7,8). This bacillus can be distinguished from R. pickettii, R. gilardii, and R. mannitolilytica by biochemical tests (nitrate reduction, carbohydrate acidification, urease, and fatty acid profile) and conclusively by DNA sequencing.…”
Section: Discussionmentioning
confidence: 98%
“…C. pauculus is the species most likely to be isolated (6). In 1999, C. pauculus was firstly described as Ralstonia paucula; the description was identical to the one given by Vaneechoutte et al in 2004 as Wautersia paucula, and it was finally renamed C. pauculus. C. pauculus is an oxidase, catalase, citrate, and urea positive motile and non-fermentatile bacillus (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang, et al [40]; Nouri, et al [41] and Vaneechoutte, et al [42] also reported R. solanacearum to be negative in starch hydrolysis. These results can be attributed to the absence of some exoenzymes (amylases) by R.solanacearum [43].…”
Section: Starch Hydrolysis Testmentioning
confidence: 99%
“…4 Cupriavidus metallidurans has the ability to survive in millimolar concentrations of heavy metals. 5 Comamonas testosteroni can accumulate poly-hydroxybutyrate in the cell. 6 Burkholderia multivorans has been known to colonize the lungs of cyctic fibrosis patients.…”
Section: Discussionmentioning
confidence: 99%